Debat Beradab Menghadapi Kaum Liberal Islam di Indonesia: Studi Kasus INSISTS Jakarta - Akhmad Rofii Damyati; Shohebul Hajad (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2023)
Due to different worldviews on knowledge, various parties often debate each other. In Indonesia, anti-mainstream groups often appear to challenge a common thought in Islam, whether religious, scientific, political, or philosophical. Liberal Islam is one of the prototypes that engage in debate in all sectors of already established thought in society, especially in Islamic issues, even fundamental issues such as faith. Due to its anti-mainstream nature, the emergence of Liberal Islam has drawn controversy and debate, especially among Liberalists from the West who brought ideas of freedom of thought. Some confronted their ideas with lengthy debates but often ended in protracted animosity. It is because the method of debate used tends not to consider the adab of arguing as taught by Islamic intellectuals. Yet, attempts at confrontation with them by taking a wiser path have been carried out by some activists of Islamic thought. Among them is INSISTS Jakarta, a research and publishing institution that has confronted the Liberal Islam discourse since the 2000s, not by way of confrontation but by counterarguments through scientific publications and seminars. This article will reveal the virtuous debate that has been carried out by these scientific institutions.